Pengaruh Metode Role Playing Terhadap Minat Belajar Siswa Kelas IV Tema 4 “Berbagai Pekerjaan” Subtema 2 “Pekerjaan Di Sekitarku” di MI Sultan Agung Sidomoro - Ngainun Fawziyah; Oky Ristya Trisnawati; Nadia Raifah Nawa Kartika (IAINU Kebumen, 2022)
This study aims to determine the effect of the Role Playing in integrated thematic learning ontheme 4 sub-theme 2 in class IV MI Sultan Agung Sidomoro in the academic year 2020/2021. Thisresearch applies experimental research with Pre-Experimental Design in the form of PreExperimental One-Group Pretest-Posttest Design. The research instrument carried out was usingdata collection techniques through observation, questionnaires, interviews, documentation,normality testing of the data was carried out using the Kolmogorov Smirnov test and hypothesistesting using the Paired Sample Test or Sample Difference using the SPSS software version 25.The results obtained that there is an effect of the method on students' interest in learning with asignificance value of Sig.(2-tailed) of 0.001 and the value <0.005 then Ho is rejected and Ha isaccepted.